Economic analysis of managerial measures in the organization - Pardupa, Martin; Jílková, Jiřina, 1956-2022; Vorlíček, Jan, 1973-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2010)
This dissertation is thus aiming to create a (1) view on current and historical theoretical and practical approaches of organization economics, (2) to assess their assumptions and implications and explain their contradictions in relation to individual base of the knowledge and motivation. (4) It suggests a framework that might give an economic and theoretical rationale to various managerial measures related to the true ("effective") effort of an individual in a firm that is (5) finally tested in empirical research. For the reasons mentioned above, the overview of often divergent methodological approaches is of a key importance, therefore much attention is dedicated to their description and analysis in the first part of the thesis. It is followed by the introduction of a new framework used in the analysis of various managerial measures applied in the firm, and finally, the hypotheses which test certain assumptions of the framework on empirical data. The "effective effort, cooperation and rivalry framework" is the main output of this thesis, as it explains the roots and influence of direct and indirect managerial measures through the behavior of workers (rivalry, cooperation, rent-seeking) on company's performance. The framework combines three existing independent approaches analyzing the link between managerial measures and company's performance without denying any of the predecessors, and it also brings a new interpretation of the functions of managerial decisions in the firm and the link on material resources.
The framework attempts to answer the following research question: Which factors and in a what way influence the effective effort of an individual in the firm? Can this approach be formalized and tested on empirical data? Answering this question would be beneficial for both managers and academia as it would facilitate them to undertake that managerial measures, that would lead to an improvement of firm's long term performance and avoid those actions, which would work contradictory. The empirical analysis focuses on efficiency of several types of incentives and trainings in the medium-sized company on the lowest level of hierarchy (furthermore there is the lack of similar analyses dedicated to an enterprise in Central and Eastern Europe or in such chronological extent in a single firm anywhere in Europe). The extensive data is provided by a leading Czech (mostly retail) betting company operating in a legislatively stable environment not exposed to the currency fluctuations and economic cycle with oligopolistic characteristics. Other industries (besides retail) would hardly provide such high quality data for such a long period suitable for the chosen analysis of the revenues' influence of various managerial measures (training of sale staff, introduction of an upside component of wage, nonmonetary rewards) applied to workers. The results of the empirical analysis show the possible positive effect of increased wage variability on the employee's performance, although the effect of training and nonmonetary rewards was proven as insignificant. These results (positive/negative effect or significance/insignificance) for a low skilled workforce being able to effectively affect the quality of the output (as is the Fortuna case) are in line with the Effective effort, cooperation and rivalry framework.
Vedoucí práce: Jiřina Jílková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: hospodářská politika [obor disert. práce]; disertace; dissertations